Survey of the arboreal species of the Federal University of Bahia, Salvador, Bahia - Carvalho, Gabriel Martins de; Roque, Nádia; Guedes, Maria Lenise Silva (SITIENTIBUS série Ciências Biológicas, 2007)
The urban green areas are important for the maintenance of the microclimate, reduction of the sonorous pollution, for the improvement of human life quality and as shelter to several animals. The Federal University of the Bahia, inserted in a major urban center, is composed by green areas and small forest fragments. The main objectives of this study are to register the arboreal species found on the UFBA and to collaborate with the knowledge of the flora of green areas located in urban centers. We collected arboreal specimens with DBH e” 10 cm, between August 2005 and June 2006, present in squares, buildings and street gardens. Species were identified and included at ALCB Herbarium. A total of 131 species distributed within 100 genera and 31 families of angiosperms and two families of gymnosperm were collected. The most diverse families were Leguminosae (30%), Arecaceae (14%), Moraceae (7%), Bignoniaceae (5%) and Malvaceae (5%). Amongst the species sampled, 65 species (49,6%) were exotic indicating that the landscape managements of the UFBA followed the standards observed in the majority of the public green areas of the Brazilian cities. Landscape interventions should prioritize the use of the native flora and take into account the natural density and distribution of the species, therefore avoiding to compromise landscape attributes and the ecological dynamics of the vegetation and related communities.